THE EDUCATIONAL PROCESS OF THE CEBU STATE COLLEGE OF SCIENCE AND TECHNOLOGY SYSTEM IN CONFORMANCE WITH THE PHILIPPINE QUALITY AWARD CRITERIA: PROPOSED MODEL - Quiros, Wenceslao M (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 11 No. 3-4, 2008, 2008)
This study was conducted to assess the educational process of the three campuses of the Cebu State College of Science and Technology System located in the northern part of Cebu namely: Carmen Campus San Francisco Campus; and Daanbantayan Campus whether it conform with the seven categories of the Philippine Quality Award Criteria. In the categories of Leadership, Strategic Planning, Faculty and Staff Focus, and, Process Management, the overall findings showed that the three sets of respondents of Carmen, San Francisco and Daanbantayan Campuses were in Moderate Conformance in addressing these categories. In the categories of Student, Stakeholder, and Market Focus, Measurement, Analysis, and, Knowledge Management; and Organizational Performance Results, the overall findings showed that Carmen Campus was in Partial Conformance in addressing these categories. It was also found out that San Francisco and Daanbantayan Campus were in Moderate Conformance in attaining these categories. There was no significant difference among the perceptions of the three sets of respondents from the three campuses. There was a significant difference among the perceptions of the three sets of respondents from the three campuses on the other six categories of PQA. On Leadership; Strategic Planning; Faculty and Staff Focus, and Process Management. The three campuses showed an effective, systematic approach, responsive to the current and changing educational service needs. On Student, Stakeholder, and Market Focus; Measurement, Analysis and Knowledge Management, San Francisco, and Daanbantayan Campus showed an effective, systematic approach, responsive to the current and changing educational service needs. On Organizational Performance Results. San Francisco and Daanbantayan Campus current performance is of high-quality in areas of importance to the college requirements. Most improvement trends and/or current performance levels are sustained. While in Carmen Campus, improvement trends are reported for most areas of importance to the organizational requirements. No pattern of adverse trends and no poor performance levels are evident in the areas of importance to the key organizational requirements.